Transcriptional analysis of murine biliary atresia identifies macrophage heterogeneity and subset-specific macrophage functions - Gromer, Kyle D.; Chen, Shang-Yang; Gadhvi, Gaurav; Feng, Liang; Shearn, Colin; Antala, Swati; Wechsler, Joshua B.; Cuda, Carla M.; Mack, Cara L.; Sokol, Ronald J.; Janssen, William J.; Green, Richard M.; et al. (Frontiers in Immunology, 2025)
IntroductionMacrophages play an important role in disease progression of pediatric cholestatic liver disease, particularly biliary atresia (BA); however, the restorative versus pathogenic role for precise macrophage subsets remains poorly defined. We aimed to distinguish the transcriptional profiles and roles of defined macrophage subset(s) in murine BA.MethodsWe used multiparameter flow cytometry and RNA-sequencing analysis to profile recruited CD11bhiCD64+ hepatic macrophages by cell surface expression of MHCII and Ly6c in the Rhesus rotavirus (RRV)-induced murine model of BA versus saline controls. Modulation of macrophage numbers via intra-peritoneal injections of clodronate-loaded liposomes was performed to determine the association between macrophage numbers and histologic injury (Ishak score).ResultsLy6c+ macrophages demonstrated the greatest increase in numbers and percent of total macrophages in murine BA versus saline controls whereas MHCII+ macrophages decreased. Transcriptional changes in murine BA MHCII+ macrophages included reduced expression of the Kupffer cell gene signature, lower expression of genes involved in homeostatic processes, and increased expression of genes involved in inflammatory processes. Ly6c+ macrophages in murine BA showed increased expression for Hif1a and other genes involved in the cellular response to hypoxia. Among all subsets, the number of Ly6c+ macrophages exhibited the strongest correlation with severity of histologic liver injury by Ishak score.ConclusionsOur data identify specific pathways upregulated in Ly6c vs MHCII+ macrophage subsets in murine BA. Transcriptional similarities between murine BA and human cholestatic macrophages may enable translation of future mechanistic studies to new macrophage subset-specific therapies.